Exploring traditional roles of first nation older adults to promote the quality of life for those experiencing alzheimer's disease and related dementia's - Cornect-Benoit, Ashley (Laurentian University of Sudbury, 2017)
The emergence of Alzheimer's disease and related dementia’s (ADRD) in Indigenous populations across Canada is a rising concern as prevalence rates exceed those of non- Indigenous populations. Culturally appropriate approaches to address the increased prevalence of ADRD are guided by the Indigenous Wholistic Theory and the Intergenerativity Model. Community-based participatory action research led by interviews, focus groups and program observations aid in identifying barriers and facilitators of success for intergenerational social engagements in the Anishinaabe community of Wikwemikong, Ontario. A qualitative thematic analysis guides future recommendations for programming opportunities to foster traditional roles of older First Nation adults and intergenerational relationships. This project results in culturally appropriate suggestions to improve healthy brain aging in older populations through increased social interactions with youth and the nurturing of traditional roles. The results of this study are relevant to other Indigenous communities who may wish to adopt the framework to their own community context. Master of Science (MSc) in Interdisciplinary Health